Long-Term Efficacy and Safety of Biodegradable-Polymer Biolimus-Eluting Stents. Issue 1 (6th January 2015) - Kaiser, Christoph; Galatius, Soeren; Jeger, Raban; Gilgen, Nicole; Jensen, Jan Skov; Naber, Christoph; Alber, Hannes; Wanitschek, Maria; Eberli, Franz; Kurz, David J.; Pedrazzini, Giovanni; Moccetti, Tiziano; et al.
<x xml:space="preserve">Abstract</x> Background— Biodegradable-polymer drug-eluting stents (BP-DES) were developed to be as effective as second-generation durable-polymer drug-eluting stents (DP-DES) and as safe >1 year as bare-metal stents (BMS). Thus, very late stent thrombosis (VLST) attributable to durable polymers should no longer appear. Methods and Results— To address these early and late aspects, 2291 patients presenting with acute or stable coronary disease needing stents ≥3.0 mm in diameter between April 2010 and May 2012 were randomly assigned to biolimus-A9–eluting BP-DES, second-generation everolimus-eluting DP-DES, or thin-strut silicon-carbide–coated BMS in 8 European centers. All patients were treated with aspirin and risk-adjusted doses of prasugrel. The primary end point was combined cardiac death, myocardial infarction, and clinically indicated target-vessel revascularization within 2 years. The combined secondary safety end point was a composite of VLST, myocardial infarction, and cardiac death. The cumulative incidence of the primary end point was 7.6% with BP-DES, 6.8% with DP-DES, and 12.7% with BMS. By intention-to-treat BP-DES were noninferior (predefined margin, 3.80%) compared with DP-DES (absolute risk difference, 0.78%; −1.93% to 3.50%; P for noninferiority 0.042; per protocol P=0.09) and superior to BMS (absolute risk difference, −5.16; −8.32 to −2.01; P=0.0011). The 3 stent groups did not differ in the combined safety end point, with no decrease in events >1 year, particularly VLST with BP-DES. Conclusions— In large vessel stenting, BP-DES appeared barely noninferior compared with DP-DES and more effective than thin-strut BMS, but without evidence for better safety nor lower VLST rates >1 year. Findings challenge the concept that durable polymers are key in VLST formation. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01166685.